As vivências espaciais dos pescadores da comunidade de Carapanatuba-Santarém/PA - Souza, Agriane Caldeira (2024)
Studies on fishing have assumed an important role and gained visibility in academic spaces, especially in the field of human and social sciences. In Geography and in other human sciences, there are several works, such as Furtado (1993), Diegues (1983), Dorsa (2015) Cruz (2019) that are based on the “fisherman category”, in order to understand how this “subject” relates to the environment through their traditional knowledge about fishing, considering all its dimensions. Having said that, we have titled this dissertation as“The spatial experiences of fishermen from the community of CarapanatubaSantarém/Pa”, because it is in this way that we seek to understand the spaces of life and work of the fishermen of the community of Carapanatuba, from their stories, their knowledge, their traditions and the relationship they have with nature. In addition to analyzing the local cultural manifestations that contribute to the strengthening of being a fisherman. For this, we rely on the support of phenomenology, which according to Dirce Suertegaray (2005) phenomenology seeks to describe the phenomena of experience, seeks to capture the sense and meaning offered by the actors, groups involved and the experience. Phenomenology creates bridges so that we have access to the most accurate information and perceptions to listen, look, feel, perceive and evaluate all the phenomena that permeate the research. As a category of analysis we chose space and place. TUAN (2012) tells us that space and place are familiar and indicate common experiences. Place is security and space is freedom. Space is more abstract than place. In addition to making use of these concepts based on authors such as Milton Santos (2002), Marcelo Lopes de Souza (2018). The work also covers concepts of memory and identity, elements that were important for the construction of the research, so that memory was a very relevant element in the construction of the narratives of our interviewees, as we worked with orality, and memory was a source important for this acquisition of information and for the analysis of an identity construction. The dissertation is divided into three chapters, which present the methodological paths taken to acquire the required information, demonstrating the life spaces of Carapanatuba fishermen and their fishing life experiences. As a result, we realized that fishing directly influences the existing dynamics in the place. We understand that this millennial activity contributes to the construction of individual and collective relationships in the place, and that it is closely linked to ways of life, as well as being/knowing/doing fisherman. It is from the relationships between them and with the different places of life and work that these subjects define themselves, organize themselves and reorganize themselves as a social group, and that they are recognized by the other social groups.